Probiotic strains with hypocholesterolemic activity as potential basis of functional food products for prevention and concomitant treatment of pathological conditions associated with high cholesterol levels - Starovoitova, Svitlana; Spivak, Mykola (My University, 2023)
So far as cholesterol-lowering activity of the studied probiotic strains and their compositions ranged between 40-78%, it should be noted that the cholesterase activity of the other studied strains was not lower, and in some cases even higher than that of most drugs currently used in cholesterinosis: Rosuvastatin, Lovastatin, Fluvastatin, Atorvastatin etc. Thus, the selected cultures of probiotic lactic acid bacteria and their compositions could potentially be used to create on their basis new effective functional food products and probiotics, as well as dietary supplement, to reduce serum cholesterol in humans. Probiotics that contain cholesterol-assimilating strains of lactic acid bacteria can efficiently complete the complex therapy of patients with cardiovascular, cancer and other diseases. Such products and drugs are devoid of the negative side effects inherent in statins, especially hepatotoxicity, they are not addictive and do not require lifelong use. Also, functional food products enriched with such probiotic microorganisms with hypocholesterolemic activity can be used not only in therapy, but also in the prevention of diseases associated with high levels of serum cholesterol. And as you know, prevention is the best, health-friendly and effective treatment for any disease.// Оскільки холестеринознижувальна активність досліджуваних пробіотичних штамів та їх композицій коливалася в межах 40-78 %, слід зазначити, що холестеризна активність інших досліджених штамів була не нижчою, а в деяких випадках навіть вищою, ніж у більшості препаратів. в даний час використовуються при холестерінозі: Розувастатин, Ловастатин, Флувастатин, Аторвастатин та ін. Таким чином, відібрані культури пробіотичних молочнокислих бактерій та їх композиції потенційно можуть бути використані для створення на їх основі нових ефективних функціональних харчових продуктів і пробіотиків, а також дієтичної добавки для зниження рівня холестерину в сироватці крові людини. Пробіотики, які містять холестерин-асимілюючі штами молочнокислих бактерій, можуть ефективно завершувати комплексну терапію хворих на серцево-судинні, онкологічні та інші захворювання. Такі продукти і препарати позбавлені негативних побічних ефектів, властивих статинам, особливо гепатотоксичності, вони не викликають звикання і не потребують довічного прийому. Також функціональні харчові продукти, збагачені такими пробіотичними мікроорганізмами з гіпохолестеринемічною активністю, можуть бути використані не тільки в терапії, але і в профілактиці захворювань, пов'язаних з високим рівнем холестерину в сироватці крові. А як відомо, профілактика – найкраще, безпечне для здоров’я та ефективне лікування будь-якої хвороби.
Keywords: hypocholesterolemic activity; probiotic strains; functional food; cholesterol; гіпохолестеринемічна активність; пробіотичні штами; функціональні продукти харування; холестерин; кафедра біотехнології і мікробіології